Multicultural Values in English Textbook for Senior High School: A Critical Discourse Analysis - Eva Listiani; Bambang Widi Pratolo (Institut Agama Islam Negeri Palopo, 2025)
This research examines the representation of multicultural values ​​in the 12th-grade high school English textbook